Hubungan Status Gizi dengan Kejadian Infeksi Saluran Pernapasan Akut (ISPA) pada Balita di Puskesmas Panteraja Kabupaten Pidie Jaya - Zakia Ulrahmah; Hafni Zahara; Rosalia Putri; Miftahul Jannah; Nurnarita Laila (Public Health Journal, 2026)
Acute Respiratory Tract Infection (ARI) remains a major health problem in Indonesia. Based on the 2025 national health reporting system survey, ARI ranks first the disease with the highest number of cases, namely more than 14.5 million cases. This study aims to determine and analyze the relationship between nutritional status and the incidence of ARI in toddlers in the working area of the Panteraja Community Health Center, Pidie Jaya Regency. The study used a quantitative method with an analytical observational design and a case-control approach. The dependent variable was the incidence of ARI in toddlers, while the independent variable was nutritional status. The study sample consisted of 66 toddlers. The results of the chi-square test showed a significant relationship between nutritional status and the incidence of ARI (p = 0.000; OR = 13,333, 95% CI = 4,028 –44,131). These findings indicate that poor nutritional status plays a role in the incidence of ARI in toddlers. Therefore, preventive promotive efforts and regular monitoring of toddler nutrition are needed to reduce the risk of ARI.